2017
DOI: 10.1177/2055217317715050
|View full text |Cite
|
Sign up to set email alerts
|

Multiple sclerosis epidemiology in Latin America: An updated survey

Abstract: Novel epidemiological data have appeared in recent years in Latin America (LATAM). The objective of this study was to perform an updated systematic review of the epidemiology of the disease reported in LATAM.MethodsWe conducted a systematic review of published epidemiological articles from January 1995 to December 2016.ResultsIncidence data were found in four studies and ranged from 0.3 to 3 annual cases per 100,000 person-years. Prevalence was reported in 13 studies and ranged from 0.83 to 38.2 cases per 100,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 54 publications
0
28
1
2
Order By: Relevance
“…This overall increase could be partially explained by female incidence estimates rising from 8.4/100,000 in 2013 to 9.8/100,000 in 2016, while male incidence has remained somewhat more stable, around 3.7/100,000, during that same time period. Nevertheless, a slight incidence increase over time has also been reported in Argentina and Panama in a recent update on MS in Latin America [16]. Reviewing the only 3 MS incidence studies in the Caribbean and Latin America, the authors also found an increase in MS incidence in Panama over a 16-year period (1990–1999 and 2000–2005) from 0.3/100,000 to 0.5/100,000 (Gracia et al [10]) and in Buenos Aires, ­Argentina from 1.8/100,000 in 2010 [17] to 3.0/100,000 in 2016 [18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This overall increase could be partially explained by female incidence estimates rising from 8.4/100,000 in 2013 to 9.8/100,000 in 2016, while male incidence has remained somewhat more stable, around 3.7/100,000, during that same time period. Nevertheless, a slight incidence increase over time has also been reported in Argentina and Panama in a recent update on MS in Latin America [16]. Reviewing the only 3 MS incidence studies in the Caribbean and Latin America, the authors also found an increase in MS incidence in Panama over a 16-year period (1990–1999 and 2000–2005) from 0.3/100,000 to 0.5/100,000 (Gracia et al [10]) and in Buenos Aires, ­Argentina from 1.8/100,000 in 2010 [17] to 3.0/100,000 in 2016 [18].…”
Section: Discussionmentioning
confidence: 99%
“…The estimated 2016 cumulative prevalence of MS in PR is the highest among countries in the Caribbean and Latin America [16]. Prevalence estimates in this region ranges from a low of 0.75/100,000 in Guayaquil, Ecuador [32] to a high of 38.2/100,000 in Buenos Aires, Argentina [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent systematic review published in 2017 estimates the epidemiological characteristics of MS in Latin America, based on the results available from seven countries . This study shows that the incidence of MS in Latin America fluctuates in the range of 0.15 to 3 annual cases per 100 000 person‐years . Likewise, the estimated prevalence was in the range from 0.75 to 38.2 cases per 100 000 person‐years .…”
Section: Introductionmentioning
confidence: 75%
“…The aetiology of MS is unknown, but there are several hypotheses that account for epidemiological and environmental factors, such as infections and genetics . A recent systematic review published in 2017 estimates the epidemiological characteristics of MS in Latin America, based on the results available from seven countries . This study shows that the incidence of MS in Latin America fluctuates in the range of 0.15 to 3 annual cases per 100 000 person‐years .…”
Section: Introductionmentioning
confidence: 81%